Factors affecting foreign direct investment on developing countries / Mohamad Razif Bakri - Bakri, Mohamad Razif (2021)
The main objective of this research is to examine the affecting Foreign Direct Investment (FDI) on developing countries. In this report, secondary data was obtained from the Malaysia Department of Statistics, the World Bank, and Economics. These studies are based on a balanced panel dataset from 1990 to 2017 in developing countries like Brazil, Pakistan, China, Indonesia, and Malaysia. The regression shows that the foreign direct investment (FDI) has major effects on the gross domestic product (GDP) and trade openness.